ANALISIS KINERJA KEUANGAN AKIBAT KETIDAKTERCAPAIAN TARGET PENJUALAN PRODUK DAUR ULANG PADA PT XYZ - Aura Safina Pratiwi; Elok Vilantika (MANAJEMEN DEWANTARA, 2026)
This study aims to analyze the achievement of sales targets and actual sales of recycled products and to examine the impact of unmet sales targets on the financial performance of PT. XYZ. The study employs a qualitative approach using a case study method. Data were collected through interviews with key informants consisting of the Finance Manager, Marketing Manager, and Production Supervisor, as well as documentation of sales reports and company financial statements. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results indicate that the realization of recycled product sales in several periods did not reach the targets set by the company. This condition is influenced by both internal and external factors, such as fluctuations in raw material prices, unstable market demand, and constraints in the production process. The failure to achieve sales targets has an impact on the company’s financial performance, particularly in the form of decreased revenue, increased production costs per unit, and declining gross profit. In addition, this condition also affects operational efficiency and the stability of the company’s cash flow.